2011
DOI: 10.1007/s10522-011-9342-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-deoxyglucose and dehydroepiandrosterone on intracellular NAD+ level, SIRT1 activity and replicative lifespan of human Hs68 cells

Abstract: 2-Deoxy-D-glucose (2-DG) and dehydroepiandrosterone (DHEA) have been hypothesized to extend lifespan via mimicking calorie restriction (CR). Activation of sirtuins has been proposed to contribute to life extension of CR by increasing intercellular levels of NAD(+) in several organisms. However, it is unclear whether 2-DG and DHEA may affect intracellular NAD(+) levels and human sirtuin 1 (SIRT1) activities. Here, using human fibroblast Hs68 cells we showed that 2-DG increased intracellular NAD(+) levels in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…To investigate how severe energy depletion affects Sirt1 activity, we replaced glucose (25 mM) with 2-DG (25 mM) rather than adding 2-DG to the glucose-containing media44. Two hours later, we visualized deacetylation of three Sirt1 substrates, p53 (K382) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate how severe energy depletion affects Sirt1 activity, we replaced glucose (25 mM) with 2-DG (25 mM) rather than adding 2-DG to the glucose-containing media44. Two hours later, we visualized deacetylation of three Sirt1 substrates, p53 (K382) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of ER stress induction by 2‐DG at 10 μM concentration may be partially due to the increased SIRT‐1 expression [Ghemrawi et al, ]. A study by Yang et al [] has revealed SIRT‐1 to be a redox sensor, dependent on the metabolic status of the cell. They have reported that, in fibroblasts, 2‐DG causes activation of SIRT‐1 in a NAD + dependent manner, mimicking a calorie restriction effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that CR, by increasing the levels of intracellular NAD, could stimulate SIRTUIN activity, and then extend the lifespan of organisms, (Lin et al, 2000; Longo et al, 2015; Lu and Lin, 2010). Recently, it was reported that a CR mimetic, 2-deoxyglucose (2-DG), can extend the replicative lifespan of Hs68 cells by increasing intracellular NAD and SIRT1 activity (Yang et al, 2011). However, several other mechanisms, independent of SIRTUINS, have also been implicated in the biological effects of CR, including inhibition of the IGF-1 pathway and modulation of the AMPK-mTOR pathway (Longo et al, 2015).…”
Section: Interventions To Prevent Age-related Nad Declinementioning
confidence: 99%